Slam as an instrument for the re-existence of the deaf community - Teixeira Iachinski de França, Luci; Leite, Maria Alzira (The ESPecialist, 2024)
Slam is a competition in which poets (slammers) recite a work of their own authorship, which goes through a commission that qualifies and judges such performances and writings. The poems address contemporary and social themes, based on the poets’ experiences. This essay aims to present an overview of how slam has been an instrument for strengthening the identity of the deaf community, whose subjects belong to a linguistic and cultural community distinct from that of hearing people. In the analysis, we observed that the representations portray the strengthening of their struggle for re-existence in favor of identity empowerment. The results point to a scenario of recognition of deaf culture and literature that has been transgressing the hearing social order through this art called slam.